Images of an Era: The American Poster 1945-75. - Cogswell, Margaret; Glaser, Milton; Ashton, Dore; Gowans, Alan (Washington : National Collection of Fine Arts - Smithsonian Institution, 1975)
Shahn, Ben ; Nitsche, Erik ; Shahn, Ben ; Bayer, Herbert ; Ackoff, Milton ; Krikorian, George ; Binder, Joseph ; Rand, Paul ; Wheeler, Dennis ; Ives, Norman ; Indiana, Robert ; Glaser, Milton ; etc.
Images of an Era: The American Poster 1945-75, Corcoran Gallery of Art, Washington, November 21, 1975 - January 4, 1976 ; Contemporary Arts Museum, Houston, February 2 - March 9, 1976 ; Museum of Science and Industry, Chicago, April 1 - May 2, 1976 ; Grey Art Gallery and Study Center, New York University, New York, May 24 - July 7, 1976. The exhibition will be shown in London and Aberdeen during the Autumn, of the Bicentennial Year 1976; in Bergen, Oslo, Munich, Aalborg, Vienna and Amsterdam in 1977 ; and in Humlebaek, Hamburg, Paris and Spoleto in 1978, all under the auspices of the Naitonal Collection of Fine Arts, Smithsonian Institution, Washington, D.C.
Duits & Engels
kunstcatalogus
Keywords: Amerika